ANALYSIS OF VISUAL REPRESENTATIONS OF WATER TOPICS IN JUNIOR HIGH SCHOOL SCIENCE TEXTBOOKS: IMPLICATIONS FOR SCIENCE LITERACY AND POTENTIAL MISCONCEPTIONS - Lestari, Putri; Laelasari, Iseu (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
The low performance of Indonesian students in the PISA 2022 science assessment highlights ongoing challenges in science literacy, especially in interpreting scientific visuals. Textbooks, as the primary learning resource, play a vital role in shaping students’ conceptual understanding. This study examines how water related topics are visually represented in junior high school science textbooks and explores their implications for science literacy and potential misconceptions. A descriptive qualitative method was applied using purposive sampling of nine BSE textbooks published by the Ministry of Education and Culture, covering grades VII–IX in both the 2013 and Merdeka (Indonesian independent) curricula. Visual data were classified into four categories: water, water and society, technology, and sustainability and responsibility. Content analysis was conducted with a coding instrument validated by two experts, one in water literacy and the other in science learning and the data were analyzed using the Miles and Huberman model with RStudio support for visualization. In total, 104 visuals were identified. The majority (63%) belonged to the “water” category, while “water and society” (17%), “technology” (12%), and “sustainability and responsibility” (8%) were underrepresented. Both curricula concentrated visuals in grade VII, with fewer in grades VIII and IX. Common inaccuracies included incomplete water cycle diagrams that omitted infiltration and percolation processes, potentially fostering misconceptions. These findings indicate that textbook visuals emphasize conceptual aspects of water while neglecting social, technological, and sustainability dimensions. This imbalance restricts students’ opportunities to develop comprehensive science literacy. The study underscores the need for more accurate, contextual, and real world aligned textbook visuals to support curriculum goals and reduce misconceptions.